A reference dataset for verifying numerical electrophysiological heart models - Paetsch Ingo; Jahnke Cosima; Kosch Olaf; Bousseljot Ralf-Dieter; Koch Hans; Fleck Eckart; Schnackenburg Bernhard (BioMedical Engineering OnLine, 2011)
Abstract Background The evaluation, verification and comparison of different numerical heart models are difficult without a commonly available database that could be utilized as a reference. Our aim was to compile an exemplary dataset. Methods The following methods were employed: Magnetic Resonance Imaging (MRI) of heart and torso, Body Surface Potential Maps (BSPM) and MagnetoCardioGraphy (MCG) maps. The latter were recorded simultaneously from the same individuals a few hours after the MRI sessions. Results A training dataset is made publicly available; datasets for blind testing will remain undisclosed. Conclusions While the MRI data may provide a common input that can be applied to different numerical heart models, the verification and comparison of different models can be performed by comparing the measured biosignals with forward calculated signals from the models.